Diseño de un Plan de Mantenimiento Preventivo Basado en la Metodología 5qs para los Equipos y Maquinaria de la Planta de Trituración Esgamo S.A.S - González Lozano, Juan Pablo; Andrade Muñoz, Jonathan (Universidad Antonio Nariño, 2022)
The creation of this preventive maintenance plan for the company ESGAMO SAS, was carried out to identify and prevent possible failures, thus reducing the number of stops and their times, applying a preventive maintenance technique called the LEM system (Lubrication, electrical and mechanical), this technique was previously studied and agreed together with the maintenance team, operators, assistants to preserve the good condition and operation of the machines and equipment.